Validation of salivary glucose as a screening tool of diabetes mellitus - Choudhry Afreen Arshad; Kumar Pradeep; Prasad Mahendra; Mohapatra Tapan; Sharma Preeti (Romanian Journal of Internal Medicine, 2022)
Background: Improved prognosis and delay of clinical complications in diabetes mellitus can be ensured by early screening and regular monitoring after diagnosis. This requires venipuncture at regular intervals of time causing anxiety and discomfort to the patient. Hence, development of a painless, non-invasive procedure is desirable for which saliva is a potential tool. Also, this would provide easy and cost-effective means for large scale screening and epidemiological intervention.